PENGARUH DIMENSI RELATIONSHIP MARKETING, KUALITAS LAYANAN DAN PERSONAL SELLING TERHADAP LOYALITAS NASABAH DI BANK BRI CABANG TULUNGAGUNG - Bayu Dwihandriyanto (Universitas Islam Kadiri, 2019)
The formation of customer loyalty can be implemented through a focus on delivering value and increasing customer loyalty. Loyalty means returning and returning customers to conduct business transactions (purchases), although it may be that the company's product is not the best product in the market or has the lowest price. This